Dissolved inorganic carbon driven dynamics of calcite shell formation in 12 strains of the freshwater algae Phacotus lenticularis (Chlorophyta) - Uta Gruenert; Jan Benda; Oliver Bossdorf; Uta Raeder (PLoS ONE, 2026)
The present rise in temperature, pCO 2 and altered precipitation impact lake water alkalinity and dissolved inorganic carbon (DIC) dynamics. Such changes on carbonate chemistry have been shown to modify calcification of shell-forming phytoplankton in marine ecosystems. Similar responses in freshwater systems remain largely unexplored. In this study, we investigate the direct effects of DIC concentration changes on the calcification state of Phacotus lenticularis, a globally abundant unicellular freshwater phytoplankton. The flagellated green algae are major contributors to modern lake carbonate production during bloom formation. P. lenticularis shells have a high CaCO 3 content compared to other pelagic calcifiers and are likely more sensitive to changing lake water carbonate chemistry. We isolated 12 P. lenticularis strains and exposed them to an ecologically relevant range of DIC (0.2 to 12 mmol L -1 total scale) in a culture experiment. By means of high resolution scanning electron microscopy (SEM) and automatic image analysis we measured functional responses and strain-specific variability in response to DIC changes. All P. lenticularis strains showed reduced shell thickness by up to 60% and dissolved calcite crystals structures at declining DIC < 4 mmol L -1 , while increasing DIC > 4 mmol L -1 had no significant effect on shell morphology. We also found no dependence of growth rates up to a lethal DIC of >10 mmol L -1 , pointing to an efficient photosynthetic rate of P. lenticularis in an under-saturated as well as saturated inorganic carbon environment. Phacotus strains showed a preadaptation to ambient DIC concentrations measured in their lake of origin. Strains from the more environmentally dynamic lake Gönningersee exhibited more variable growth rates and cell densities compared to strains from the more stable Großer Ostersee. We hypothesize, that reduced availability of dissolved inorganic carbon and a lowered saturation state with regard to calcite will drive a negative calcification response in P. lenticularis . However, intraspecific variations in sensitivity to DIC changes were evident in our study and may represent a geographically available potential to adapt to new stressors.